Mothers', fathers' and children's perceptions of parents' expectations about children's family obligations in nine countries - Lansford J. (2017)
© 2015 International Union of Psychological Science Children's family obligations involve assistance and respect that children are expected to provide to immediate and extended family members and reflect beliefs related to family life that may differ across cultural groups. Mothers, fathers and children (N = 1432 families) in 13 cultural groups in 9 countries (China, Colombia, Italy, Jordan, Kenya, Philippines, Sweden, Thailand and United States) reported on their expectations regarding children's family obligations and parenting attitudes and behaviours. Within families, mothers and fathers had more concordant expectations regarding children's family obligations than did parents and children. Parenting behaviours that were warmer, less neglectful and more controlling as well as parenting attitudes that were more authoritarian were related to higher expectations regarding children's family obligations between families within cultures as well as between cultures. These international findings advance understanding of children's family obligations by contextualising them both within families and across a number of diverse cultural groups in 9 countries.